Combining space use with diet data to investigate foraging tactics of black bears in response to the pulsed availability of migratory caribou calves - Linda Nowack; Michaël Bonin; Martin Leclerc; Candice Michelot; Christian Dussault; Joëlle Taillon; John Pisapio; Steeve D. Côté (PLoS ONE, 2026)
Migratory caribou ( Rangifer tarandus ) is a key component of the arctic food web. Female caribou typically gather in late spring to give birth, creating a predictable, ephemeral resource pulse that can influence consumer behavior. As an omnivore, the black bear ( Ursus americanus ) predates on caribou neonates during calving when they are most vulnerable and occur at high densities. We studied black bears in northern Québec and Labrador interacting with the Rivière-aux-Feuilles (RAFH) and Rivière-George (RGH) migratory caribou herds. Our aim was to assess the spatial response of bears to caribou distribution during calving by investigating the potential correlation between bear movements and their relative trophic position. We expected bears with higher trophic positions to adopt behaviors favoring caribou encounters during the caribou calving period. We used GPS telemetry data from 40 bears and 319 female caribou between 2012 and 2019 to calculate movement metrics and home ranges, and to assess seasonal variation in movement patterns and shared space use between bears and caribou. We then analyzed the relationships between space use data and relative trophic position of bears obtained from stable isotope analysis of blood serum. The relative trophic position of black bears differed between study sites, with individuals in northern Québec (RAFH) exhibiting higher trophic positions than those in Labrador (RGH). Relative trophic positions varied strongly among individuals, indicating substantial individual differences in foraging strategies. Greater proportional overlap of bear ranges with caribou calving ground was associated with higher trophic positions, while higher use of caribou-preferred habitat by bears surprisingly correlated with lower relative trophic positions. The absence of a clear link between movement metrics and trophic position may reflect the inherently opportunistic foraging behavior of black bears. Additional research at the individual level is needed to gain deeper insight into black bear foraging strategies in response to pulsed resources.